Catálogo das louças salvaguardadas na Reserva Técnica III do Museu Municipal Parque da Baronesa (Pelotas/RS) - Bosenbecker, Angelica Soares (2016)
This work it is about the study of the dinnerware safeguarded in Technical Reserve III of the Park of Baronesa Municipal Museum, located in Pelotas/RS. The research has been carried out following paths presented in the subjects of Archeology, Museology and Conservation and Restoration, intending, as a final result, to make a dinnerware catalog whose information integrates museum data, related to documents about pieces available in the institution and archaeological research data, focused on the study of archaeological dinnerware, available in specialized literature on the topic. At the end of this study, information will be generated which can be included to the catalog created for this type of material in order to be added to other already done studies and to serve as a source for future research.